Pelatihan Pemanfaatan Media Audiovisual sebagai Sarana Pembinaan Remaja Masjid di Barisan Mujahid Matita - Dani Manesah; Silvia Lestari; Suryanto, Suryanto; Leni Deli; Emi Masyitah; M. Irfan Aldy Nasution; Tara Dwi Shapira; Petra Putri Sari Buulolo; Soeheri Soeheri (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of digital technology has brought significant changes to the delivery of da'wah messages to young people. Audiovisual media has become an effective means of attracting interest, enhancing understanding, and increasing the participation of mosque youth in development activities. This service aims to analyze the use of audiovisual media as a means of developing mosque youth at Barisan Mujahid Matita (BMM), Medan. The method used is a qualitative approach through observation and audiovisual production training, which can improve the skills of young people in creating da'wah content, strengthen understanding of development material, and boost enthusiasm in participating in mosque activities. In addition, audiovisual media has proven to help BMM enhance the quality of documentation and publication of activities. In conclusion, audiovisual media is an effective instrument in the development of young people, especially in the context of creative digital da'wah. Digital Mosque Youth